Principal stresses on the contact surface of a cam-tracker mechanism designed using Bézier curves (2018)
The study exposes the variation of the main stresses in a cam mechanism with roller follower whose profile has been designed by means of Bézier curves. The contact theory for the cam case is proposed and the distribution of the stresses throughout the cam turning cycle is presented, applied to an established study model.